Abnormal calcium metabolism in normocalcaemic sarcoidosis. Issue 6050 (18th December 1976) - Reiner, M; Sigurdsson, G; Nunziata, V; Malik, M A; Poole, G W; Joplin, G F
Abstract : In studies of calcium metabolism in 13 unselected patients with untreated sarcoidosis all were normocalcaemic but five had hypercalcuria. All had normal renal function. Calcium absorption was indexed by a double isotope test. 45Ca hyperabsorption occurred in six patients. Ten kinetic studies were carried out with 47Ca and in six bone turnover was increased. 45Ca absorption correlated well with the calculated bone uptake rate of calcium, and with urine calcium excretion. These results suggest that in sarcoidosis abnormalities in calcium metabolism are fairly common although they rarely result in sustained hypercalcaemia.